Konservasi Budaya Seni Tradisi Desa Tlogopucang Kabupaten Temanggung - Laura Andri R.M. (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
Culture is a human product as a result of community activities. The culture can be in the form of traditional art which contains knowledge, beliefs, norm values and beauty values. Indonesia is famous as a country rich in culture. In every region there are diverse cultures. Cultural heritage of ancestors is also found in the highlands of Central Java, namely Tlogopucang Village, Kandangan District, Temanggung Regency. In the area there are several traditional arts in the form of Angklung Tapak Asta, Sadranan Kyai Kramat, Razor Shear, and the Ngedun-dunke Tradition. Through a combination of historical and descriptive qualitative approaches and in-depth interview techniques, observations and documentation have found that the impediment to the inheritance of traditional culture is due to the influence of global cultural expansion. For this reason, a strategy in the form of inventory and revitalization is needed so that traditional arts can survive and can strengthen the identity of the community